Modeling the health impact of legislation to limit the salt content of bread in Portugal: A macro simulation study - Francisco Goiana-; Francisco Goiana-; David Cruz-; Ana Rito; Carla Lopes; Carla Lopes; Magdalena Muc; Ara Darzi; Fernando Araújo; Marisa Miraldo; Alexandre Morais Nunes; Luke N. Allen (Frontiers Media S.A., 2022)
BackgroundExcessive salt consumption-associated with a range of adverse health outcomes-is very high in Portugal, and bread is the second largest source. Current Portuguese legislation sets a maximum limit of 1.4 g salt per 100 g bread, but imported and traditional breads are exempted. In 2017 the Ministry of Health proposed reducing the salt threshold to 1.0/100 g by 2022, however the legislation was vetoed by the European Commission on free-trade grounds.AimsTo estimate the health impact of subjecting imported and traditional breads to the current 1.4 g threshold, and to model the potential health impact of implementing the proposed 1.0 g threshold.MethodsWe gathered bread sales, salt consumption, and epidemiological data from robust publicly available data sources. We used the open source WHO PRIME modeling tool to estimate the number of salt-related deaths that would have been averted in 2016 (the latest year for which all data were available) from; (1) Extending the 1.4 g threshold to all types of bread, and (2) Applying the 1.0 g threshold to all bread sold in Portugal. We used Monte Carlo simulations to generate confidence intervals.ResultsApplying the current 1.4 g threshold to imported and traditional bread would have averted 107 deaths in 2016 (95% CI: 43-172). Lowering the current threshold from 1.4 to 1.0 g and applying it to all bread products would reduce daily salt consumption by 3.6 tons per day, saving an estimated 286 lives a year (95% CI: 123-454).ConclusionsSalt is an important risk factor in Portugal and bread is a major source. Lowering maximum permissible levels and removing exemptions would save lives. The European Commission should revisit its decision on the basis of this new evidence.